A new genus and species of Sieblosiidae from the Middle Miocene of Germany (Odonata: Epiproctophora) - Nel, André; Fleck, Gunther (Zootaxa, 2012)
Germanostenolestes lutzi, new genus and species of Sieblosiidae is described from the Middle Miocene of Öhningen (Germany). It probably belongs to the clade (Paraoligolestes + (Parastenolestes (Germanolestes + Stenolestes))) sensu Nel et al. (2005). It is the third representative of the Sieblosiidae described from this outcrop, showing that this family was still quite diverse in the Middle-Late Miocene.